A Neonate with Large Oral Cavity Teratoma – An Anesthetic Challenge - G. Kasirajan (Journal of Integrated Health Sciences)
An 18-day-old female baby presented with a swelling arising from the hard palate; and presenting with a difficult breast feeding and difficult airway or obstruction is a rare condition. It may range from a simple dermoid cyst to malignant neoplasms. Airway management of this baby was very difficult and quite challenging. The airway was secured with inhalation induction and spontaneous ventilation.